O comportamento lingüistico na comunidade bilíngüe ítalo-brasileira de Nova Pádua/RS : identidade, prestígio e estigma lingüísticos - Toscan, Mirian Peccati (My University, 2014)
This reasearch was developed in an Italo-Brazilian linguistics community of Nova Pádua, located in the northeast of Rio grande do Sul, which was founded in 1885 by Italian imigrants. This etnolinguisitcs group lives with a situation of bilinguism and languages in contact with each other. The aim of our work was to investigate the linguistics attitudes of the bilingual speakers in relation to the used speaking systems by the ethnic-social: the standard Portuguese language, the Italian dialect (Coiné) and the variety of the local speaking Portuguese language. The investigation began with the presupposition that bilingual speakers have positive or negative attitudes, prestige or stigma, in relation to the linguistics varieties. Besides this, we presupposed that bilingual speakers behaviour is measured by the values given to the languages. The results showed a series of positive and negative values related and perceived in the linguistics varieties. Not just the positive and negative evaluation guides the linguistics behaviour of bilingual speakers, but also extra-linguistics factors as a formal interation situation or the speaker s solidarity. Surprisingly, the research showed a conflict of values and linguistics identity in the sample. This conflict was revealed in the contradiction of the values judgement given to the linguistics varieties in the two evaluation proposals suggested by the research. In the first proposal, where the speaker is a third person, not the one belong to the research, the Italian dialect is the speaking system of the greatest prestige and the standard Portuguese language, the language of minor prestige. The positive attitudes in relation to the Italian dialect direct to an afective link between the Italian ethnic feeling and the sample s linguistic identity. Contradictorily, for an interpersonal situation, in usual dominions as house, school, chapel where the own bilingual should speak, the values differ. It means that the regional and standard Portuguese language speaking systems receive more prestige than the Italian dialect. Among other aspects, these attitudes were justified by the necessity of the Portuguese language dominium, by the speakers solidarity and by the recognition of a linguistics form of a local Portuguese language, Portuguese with Italian marks. By all these, the dates showed that the Italian linguistics identity is more idealized and/or nostalgic than real.On the other side, it seems appearing a latent recognition of a local Italo-Brazilian linguistcs practice.
Esta pesquisa foi desenvolvida na comunidade lingüística ítalo-brasileira de Nova Pádua, situada Nordeste do Rio Grande do Sul, fundada em 1885 por imigrantes italianos. Esse grupo etnolingüístico convive com uma situação de línguas em contato e bilingüismo. O objetivo deste estudo foi investigar atitudes lingüísticas dos bilíngües em relação aos sistemas de fala utilizados pelo grupo étnico-social: a língua portuguesa standard, o dialeto italiano (Coiné) e a variedade de fala de língua portuguesa local. A investigação partiu do pressuposto de que os bilíngües adotam atitudes positivas ou negativas, de prestígio ou estigma, em relação às variedades lingüísticas. Além disso, pressupõe-se que o comportamento dos bilíngües é regulado por valores atribuídos às línguas. Os resultados mostraram uma gama de valores positivos e negativos atribuídos e percebidos nas variedades lingüísticas, e esses valores orientam o uso dessas variedades. Não só a avaliação positiva ou negativa orienta o comportamento lingüístico dos bilíngües, mas também fatores extralingüísticos como situações de interação formal ou informal e a solidariedade ao interlocutor. Inesperadamente, a pesquisa mostrou um conflito de valores e de identidade lingüísticos entre os participantes da amostra. Esse conflito revelou-se na contradição existente nos juízos de valor atribuídos às variedades lingüísticas, nas duas situações de avaliação propostas pela pesquisa. Na primeira, em que o falante seria uma terceira pessoa e não o sujeito da pesquisa, o dialeto italiano é o sistema de fala de maior prestígio, e a língua portuguesa standard, a língua de menor prestígio. As atitudes positivas em relação ao dialeto italiano ou dialeto vêneto (Coiné) apontam para uma ligação afetiva entre o sentimento étnico italiano e a identidade lingüística da amostra. Contraditoriamente, para uma situação interpessoal, em domínios usuais como: casa, Capela, escola, em que o próprio bilíngüe deveria falar, os valores divergiram. Isto é, os sistemas de fala de língua portuguesa, local e standard, receberam maior prestígio do que o dialeto italiano. Essas atitudes foram justificadas, entre outros motivos, pela necessidade de domínio da língua portuguesa, pela solidariedade ao interlocutor e pelo reconhecimento de uma forma lingüística de língua portuguesa local, língua portuguesa com marcas italianas. Dessa forma, os dados mostraram que a identidade lingüística italiana é mais idealizada e/ou nostálgica do que real. Em contrapartida, parece surgir um latente reconhecimento de uma prática lingüística ítalo-brasileira local.
Keywords: Linguística, Letras e Artes; Sociolinguística; Grupo etnolinguístico; Nova Pádua, RS; Línguas em contato; Bilinguismo; Variedades linguísticas; Juízos de valor; Prestígio; Estigma; Atitudes linguísticas; Identidade lingüística; Interlocutor; Interação entre falantes; Sociolinguistic; Etnolinguisitcs group; Nova Pádua, RS; Languages in contact; Bilingualism; Linguistics varieties; Extra-linguistics factors; The values judgement; Prestige; Stigma; Linguistics attitudes; Linguistics identity; Interactions between speakers; Dialeto italiano